2018
DOI: 10.3233/cbm-181198
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA CASC2 expression is down- regulated in papillary thyroid cancer and promotes cell invasion by affecting EMT pathway

Abstract: Thus, these results indicated that lncRNA CASC2 was a predictor for LNM of PTC patients and may serve as a potential target of PTC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…In this study, we found that CASC2 was lowly expressed in PTC tissues and cells and indicated poor prognosis of patients, which is also in agreement with former efforts [ 14 , 15 , 18 ]. 131 I therapy is a common strategy for the treatment of thyroid cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that CASC2 was lowly expressed in PTC tissues and cells and indicated poor prognosis of patients, which is also in agreement with former efforts [ 14 , 15 , 18 ]. 131 I therapy is a common strategy for the treatment of thyroid cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Long noncoding RNA cancer susceptibility candidate 2 (CASC2) has been demonstrated as a tumor suppressor by regulating cell proliferation, apoptosis, migration, and chemoresistance in human cancers, including hepatocellular carcinoma, gastric cancer, and prostate cancer [ 11 13 ]. Furthermore, emerging evidences suggest that CASC2 is lowly expressed and inhibits cell proliferation in PTC [ 14 , 15 ]. However, little is known about the role of CASC2 in 131 I sensitivity to PTC.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can affect the stability of coding genes by regulating the activity of miRNAs, thereby regulating a variety of biological activities of tumor cells, including transcriptional regulation, post-transcriptional regulation, and phenotypic regulation (15).In previous studies, Zhou et al found that the expression of lncRNA CASC2 was associated with lymph node metastasis in PTC patients, which inhibited the proliferation, apoptosis and migration of cells (16).Also, Song et al con rmed that lncRNA ENST0000053963 could act as an oncogenic factor in PTC through MAPK signaling (17), suggesting that lncRNAs could function both as tumor suppressors and tumor promoters. In this study, according to the TCGA we newly discovered many lncRNAs aberrantly expressed in PTC tissues, of which Linc00460 may promote the invasion and metastasis of cancer, Linc00460 has been con rmed to be closely related to the progression of various cancers, such as its promotion of cell migration and invasion by regulating hnRNPK and induction of epithelial-mesenchymal transition in cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Long non‐coding RNA (lncRNA) dysfunction is related to a wide range of diseases, such as cancer, neurodegeneration, cardiovascular disease and neurasthenia . For example, overexpressed lncRNA NR_036575.1 would lead to the proliferation and migration of papillary TC . In order to discover the genes that might be correlated with TC, the Gene Expression Omnibus (GEO) database was employed to retrieve the lncRNA trinucleotide repeat containing 6C (TNRC6C)‐AS1 was overexpressed in TC cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 For example, overexpressed lncRNA NR_036575.1 would lead to the proliferation and migration of papillary TC. 7 In order to discover the genes that might be correlated with TC, the Gene Expression Omnibus (GEO) database was employed to retrieve the lncRNA trinucleotide repeat containing 6C (TNRC6C)-AS1 was overexpressed in TC cells. Therefore, lncRNA TNRC6C-AS1 was the main focus of our study.…”
Section: Introductionmentioning
confidence: 99%